Data Conversion Strategies for Effective Aviation Technical Support as a Service - Igor Kabashkin; Vladimir Perekrestov; Maksim Pivovar (Applied Sciences, 2025)
Small airlines face significant challenges in maintaining operational efficiency and ensuring compliance with regulatory standards due to limited resources, fragmented technical support ecosystems, and high operational costs. Aviation Technical Support as a Service (ATSaaS) offers an innovative, scalable framework to address these issues by providing centralized or decentralized platforms for technical support. This study examines the advantages, disadvantages, and life cycle costs of centralized and decentralized data conversion architectures within the ATSaaS model. Using mathematical models and a numerical example, the research highlights the trade-offs between initial investments and long-term operational costs, with centralized systems benefiting from economies of scale and decentralized systems offering flexibility. This study also identifies limitations and future research directions.